Cephalopod‐Inspired Miniaturized Suction Cups for Smart Medical Skin. Issue 1 (20th May 2015) - Choi, Moon Kee; Park, Ok Kyu; Choi, Changsoon; Qiao, Shutao; Ghaffari, Roozbeh; Kim, Jaemin; Lee, Dong Jun; Kim, Myungbin; Hyun, Wonji; Kim, Seok Joo; Hwang, Hye Jin; Kwon, Seung‐Hae; et al.
Abstract : Biomimetic miniaturized suction cups (mSCs) are designed for the patient friendly, dry adhesives of smart medical skin. Both strong van der Waals force and induced negative pressure by the ultrasoft mSCs facilitate tight skin coupling without discomfort or irritations, improve sensitivities of the embedded stretchable electronics for continuous vital sign monitoring, and enable multiple drug reloading without loss of the adhesion.